Design thinking sprints as a facilitation process to enact change in the residency match process and beyond - Do, Victor; Lewis, Melanie; Smith, Preston; Moineau, Geneviève (Canadian Medical Education Journal, 2023)
Implication Statement Enacting change in medical education requires effective facilitation processes. Medical education lags behind other fields in systems innovation and radically disruptive approaches to the challenges we encounter. Design thinking “sprints,” widely used in many other settings, serve as an opportunity to fill the gap as a facilitation process during periods requiring extensive and/or rapid change. Though resource-intensive, our experience using design thinking sprints for a situation requiring urgent change management with high-stakes implications for Canadian medical education to demonstrate their utility. A more widespread, adoption can contribute to innovation within all aspects of education including curriculum design, policy development, and educational process renewal.